How farmers perceive perennial weeds in Northern France and Eastern Germany - Andert, Sabine; Guguin, Julie; Hamacher, Merle; Valantin-Morison, Muriel; Gerowitt, Baerbel (Frontiers in Agronomy, 2023)
European farmers are required to follow the transition towards sustainable agriculture and food systems. Perennial weed management without chemical herbicides and inversion tillage is challenging farmers. Questions arise to cope with these spreading weeds. Our study focuses on farmers' perceptions and experiences of perennial weeds and their control in Northern France and Eastern Germany. A survey was developed to explore the situation regarding present concerns and future problems for perennial weed control. The survey conducted from winter 2020/21 to spring 2021 targeted conventional, conservation and organic farms.We found a high level of awareness for perennial weeds. On average, 80.0% of Northern France French farmers and 65.9% of Eastern German farmers revealed present concerns about perennial weeds. Both, Northern France French and Eastern German farmers perceived perennial weeds are more damaging to crop production than other pests. In both regions, the farmers considered Cirsium arvense (L.) Scop.C. arvense as the most important perennial weed. While the majority of the Eastern German farmers observed field infestations of Elymus repens (L.) GouldE. repens, Northern French farmers more often reported Sonchus . arvensis L. infestations. More than fifty percent50% of the farmers stated Rumex spp. infestations in Northern France and Eastern Germany.Interestingly, Eastern German farmers are more concerned about future perennial weed problems than Northern France French farmers. The reasons for farmer's future concerns are obvious andprobably connected to the farming system. In both regions, conservation and conventional farmers heavily rely on herbicides for perennial weed control, however, more farms used the active ingredient glyphosate in Eastern Germany. Nonetheless, perennial weed control is especially a major concern for organic farmers in both regions. hat formatiert: Französisch (Frankreich) hat formatiert: Französisch (Frankreich)